Q & A review of Surgery - Gamelli, Richard L.; Gamelli, Richard L.; Moore, Ernest Eugene; Foster, Roger S. (St.Louis : Mosby, 1995)
As a companion to surgery a problem solving approach, this question and answer book provides an opportunity to test your knowledge of surgery.
37. Abdominal Wall and Hernia / A. Gerson Greenburg -- 38. Genitourinary Disorders / Peter A. Nash and Jack W. McAninch -- 39. Gynecologic System / Linda Van Le -- 40. Heart: Congenital Disease / William R. Wilson, Jr. -- 41. Heart: Acquired Disease / Bruce J. Leavitt -- 42. Aorta and Peripheral Arteries / David B. Pilcher -- 43. Veins and Lymphatics / Michael A. Ricci -- 44. Spleen and Lymph Nodes / James C. Hebert -- 45. Breast / Roger S. Foster, Jr. -- 46. Thyroid Gland / Roger S. Foster, Jr. -- 47. Parathyroid Glands / Orlo H. Clark and Quan-Yang Duh -- 48. Adrenal Gland / David J. Dries -- 49. Pituitary Gland / David J. Dries -- 50. Endocrine Pancreas / Jeffrey A. Norton -- 51. Hand / A. Griswold Bevin.
surgery.
All age.
Keywords: Surgery -- examination questions; Critical Care -- methods -- examination questions